An unsual finding of brain magnetic resonance imaging in a hypertensive patient - Ngow, Harris Abdullah; Wan Khairina, Wan Mohd Nowalid; Hamidon, Bin Basri (Page Press, 2009)
Brain edema in patients with hypertensive encephalopathy frequently affects the parietooccipital white matter. Hypertensive encephalopathy is thus included as a differential diagnosis in reversible posterior leukoencephalopathy syndrome. Diffuse white matter involvement rarely occurs. We report a 41-year old woman with hypertensive encephalopathy with diffuse and non-enhancing white matter hyper-intensities throughout the whole brain on magnetic resonance imaging (MRI). These hyperintensities spared the grey matter on T2-weighted and FLAIR sequence. These unusual finding on brain MRI was attributed to severe vasogenic cerebral edema resulting from accelerated hypertension.